The Relationship Between Personality Traits and Job Satisfaction: Special Reference to Wso2 It Company in Western Province - Thaneswary, R.; Nirojan, J.; Vijayakumaran, R. (Faculty of Management and Commerce, South Eastern University of Sri Lanka, 2019)
The purpose of this study to present the relationship between personality traits and job satisfaction among the Software developers and Engineers in WSO2 Information Technology (IT) Company in Western Province. Quantitative approach was utilized in this study. Variables namely; openness, conscientiousness, extroversion, agreeableness and neuroticism were used as the independent variables to predict the job satisfaction. Data were collected from a sample of 249 respondents using structured questionnaire. The results of the analysis show that the relationship between personality traits and job satisfaction is in the moderate level. Most of the employees believe that the job satisfaction depends on other factors too than the personality traits. Further, personality traits contributes significantly to job satisfaction (F= 53.432; P < 0.05) with the prediction of 37.8 percent of variation. Further openness, conscientiousness, extroversion and agreeableness contributes significantly to job satisfaction rather than neuroticism. This study is limited to the sample of IT employees and Engineers and the environmental factors, economic issues and fiscal and monitoring portfolio which are not examined in this research.
Keywords: Personality Traits; Openness; Conscientiousness; Extroversion; Agreeableness; Neuroticism; Job Satisfaction